A complex intervention to improve outcome in obese pregnancies; the upbeat study. (7th June 2011) - Poston, L; Holmes, B; Kinnunen, T; Croker, H; Bell, R; Sanders, T; Wardle, J; Sandall, J; Robson, S R; Sattar, N; Nelson, S; Barr, S; et al.
Abstract : Objectives: To develop a lifestyle intervention to improve pregnancy outcome in obese pregnancies. Methods: In accord with UK MRC guidelines a phased approach towards development of an randomised controlled trials (RCT) was adopted by a multidisciplinary team. This included Phase I literature review and protocol development; Phase II pilot RCT to assess behavioural change and practicality; Phase III (multicentre RCT; primary outcomes; maternal oral glucose tolerance test ; neonatal, macrosomia, n=2700) will follow demonstration of behavioural change in the pilot. Results: An intervention based on dietary advice (low glycaemic index, low saturated fat and reduced free sugars) and increased physical activity was developed. Advice is delivered by a health trainer in eight structured sessions between 19 and 28 week's gestation and reinforced by a participant handbook, log book and physical activity DVD. Data are entered on an internet database. Recruitment to the pilot phase is complete. 136 obese pregnant women (body mass index; 36.7±6 kg/m 2 ; 47 nullips, 71 multips; age 30±5 years; 69 white; 42 black, 7 other) have been randomised to the intervention or standard antenatal care. Physical activity is monitored by accelerometry (1 week×3) and validated questionnaire, and diet by 24 h food recall (double- pass ×3). A lifestyle questionnaire in used to assess knowledge and attitudes. Behavioural changes will be analysed in Feb 2011 and presented at the meeting. Conclusion: A pilot study of a complex intervention has been successfully implemented. This step wise approach has enabled detailed development, refinement and evaluation of each component, leading to an intervention acceptable to obese pregnant women.